Khair Seedling Mortality in Plantations - Bakshi, B. K.; Ram Reddy, M. A.; Singh, Sujan; Pandey, P. C.; Mukherjee, S. N. (Indian Forester, 1968)
In plantations in the Siwalik Forest Division, U.P. State, raised on site previously occupied by scrub forests, khair seedlings suffered a mortality of 14 per cent, of which 12 per cent could be ascribed due to attack by the root parasite, Ganoderma lucidum (Leyss.) Karst. The fungus, as endemic species in the natural forests, built up in the residual stumps which served as infection centres of high inoculum potential. The decayed stumps infected khair seedlings by direct root contact and killed them. Removal of residual stumps and roots from trenches prior to planting in order to remove the source of infection will bring the disease incidence to the minimum.